Description of teacher professional competency by using media and learning resources in SD Muhammadiyah Demangan Yogyakarta in the Industry Era 4.0 - Nur Hidayah; Mona Sholihah (Faculty of Science and Mathematics, Universitas Kristen Satya Wacana, 2019)
In an effort to improve the quality of education in Indonesia, one of which can be done by increasing and developing the professional competence of teachers in the industrial age 4.0. This study aims to describe the ability of teachers to use media and learning resources as well as the barriers faced by teachers in using the media and learning resources in SD Muhammadiyah Demangan. This research is a descriptive qualitative research. Data collection methods used i.e., interview, observation and documentation. Data analysis in this research with the reduction of data, display data, and the withdrawal of the conclusion. Test the validity of the data using triangulation techniques and sources. The results showed that (1) the ability of teachers to use instructional media such as print, visual, audio-visual and games are already good just for the media game is rarely used because of the time limitations. (2) the ability of teachers using learning resources such as message/content, people/teachers, material/software,tools/hardware, engineering and the environment is already good. (3) the obstacles facing teachers namely time, funding, networking internet, interest, capabilities, characteristics and level of understanding of different students and students who do not focus or not. In addition to enhancing the competence of a teacher who is a professional in the industry 4.0 minimum teacher also has the capability of 4 c i.e. Communication, colaboration, critical thingking, and creativitas thingking in an effort to improve the quality the teachers themselves.